Improved and synergistic catalysis of single-pot-synthesized Pt–Ni alloy nanoparticles for anodic oxidation of methanol in alkali. Issue 95 (27th September 2016) - Banik, Senjuti; Mahajan, Ankita; Chowdhury, Sreya Roy; Bhattacharya, Swapan Kumar
Abstract : In the search for commercial anode materials for direct methanol fuel cells, Pt, Ni, and Pt x Ni y alloy NPs have been synthesized via one pot reduction of the respective pure and mixed metal precursors at 60 °C without adding any capping agent. Abstract : In the search for commercial anode materials for direct methanol fuel cells, nanoparticles of Pt, Ni, and Pt x Ni y alloys have been synthesized via one pot reduction of the respective pure and mixed metal precursors at 60 °C without adding any capping agent. The obtained Ni–Pt nanoalloy is stable in dispersion and powder form. The X-ray diffraction, spectroscopic and microscopic studies reveal crystallites with diameters of 4.5–8.2 nm are agglomerated in a nearly spherical shape on the base of the electrode. The electrodes constructed with the nanoalloys show excellent electrocatalytic activity in reference to the oxidation of methanol in alkaline medium. The synthesized material shows synergistic effects in catalysis and the alloy containing 20 mol% of Ni seems to be the best catalyst, which also shows promising results with respect to the oxidation of other related fuels like formaldehyde and sodium formate. The constructed electrodes are very stable throughout the reaction and even after several cycles of operation. A probable mechanism for the reaction is also suggested.